2016
DOI: 10.3389/fmars.2016.00060
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Willingness to Donate to Marine Endangered Species Recovery in the Galapagos National Park, Ecuador

Abstract: Willingness to donate (WTD) money for the conservation of endangered species may depend on numerous factors. In this paper, we analyze data from a survey given to tourists visiting Ecuador's Galapagos National Park and Marine Reserve to investigate determinants of their WTD toward the conservation of two marine endangered species-the scalloped hammerhead shark (Sphyrna lewini) and the green sea turtle (Chelonia mydas). Specifically, we use regression analysis to analyze the influence of attitudes and beliefs t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 51 publications
3
17
1
2
Order By: Relevance
“…Respondents who were members of an ENGO were willing to donate more to species and ecosystems. We did not find gender differences in WTD to species or ecosystems, which is in line with Cárdenas & Lew (). However, as previous research has brought mixed results (e.g.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Respondents who were members of an ENGO were willing to donate more to species and ecosystems. We did not find gender differences in WTD to species or ecosystems, which is in line with Cárdenas & Lew (). However, as previous research has brought mixed results (e.g.…”
Section: Discussionsupporting
confidence: 92%
“…However, there is mixed evidence about the association between ‘patriotic’ values or ethnocentrism and donation behaviour. More specifically, some authors have found donors to prefer local conservation causes (Dallimer et al ., ; Cárdenas & Lew, ), whereas others have found no evidence (Veríssimo et al ., ).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…For example, visitors to the Doñana National Park in Spain were asked to valuate 15 species, ranging from charismatic (Iberian lynx Lynx pardinus and imperial eagle Aquila adalberti) to those that generate fear (Grass snake Natrix natrix and endemic spider Donacosa merlini), yet only 27.4% of survey respondents were unwilling to pay for species conservation projects [25]. Similarly, only 19% and 25% of visitors surveyed at the Galapagos National Park were unwilling to donate to conservation efforts for green turtle (Chelonia mydas) and scalloped hammerhead (Sphyrna lewini), respectively [26]. This disparity between visitors to the Galapagos National Park and the Florida anglers currently surveyed may simply reflect demographic differences between the two groups of respondents.…”
Section: Discussionmentioning
confidence: 99%